Aluminum, nickel, and manganese supported on bentonite for conversion of ethanol to gasoline - Rahmanda, Deri; Wardhani, Sri; Andayani, Ulfa; Widjaya, Robert R.; Dwiatmoko, Adid A.; Rinaldi, Nino; Prasetyo, Joni; Kurniawan, Kezia F. (International Journal of Renewable Energy Development, 2025)
The potential of bentonite as a catalyst is rapidly growing, isomorphic substitution in its interlayer allows for cation exchange and facilitates modification to enhance its catalytic properties. The catalytic performance of bentonite can be improved through the insertion of pillared clays (PILC) into its interlayer structure using Al2O3, NiO, and MnO metal oxide alloys. This research aims to develop and study a modified bentonite catalyst, focusing on its physicochemical changes,as well as its activity and selectivity in the conversion of ethanol to biogasoline. The synthesis of oxide pillars on bentonite was carried out at a consistent metal/bentonite mole ratio of 10 mmol/g, with a mixed metal composition of 1:1. The results showed anexpansion of interlayer distance, as measured by X-ray diffraction (XRD), which increased in all catalysts compared to natural bentonite6,350 (13.94 Å). Surface Area Analyzer (SAA) analysis, revealed that Al/Bentonite exhibited the highest surface area at187.84 m2/g. Total acidity  analyzed, using Temperature Programmed Desorption-Ammonia (TPD-NH3), was found to be 2.33 mmol/g, with Al-Ni/Bentonite showing the highest acidity. Thermal stability, tested throughThermogravimetric Analysis (TGA), indicated that catalysts containing Al and Ni demonstrated the highest stability. The catalytic activity test showed that the Al/bentonite catalyst achieved the highest ethanol conversion rate of68.64% and a catalyst selectivity of 51.70%, as determined byGas Chromatography-Flame Ionized Detector (GC-FID) analysis. These results indicate that the pillarization of bentonite with Al2O3, NiO, and MnO oxides significantly improved its physicochemical properties, activity, and selectivity in the catalytic conversion of ethanol to biogasoline compared to natural bentonite.